Implementasi Teknologi Untuk Pengembangan Sumber Daya Manusia pada Korporasi - Kepler Sinaga (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Rapid changes in human technology affect countless businesses, the strength of a company can be measured by the level of technology applied for efficiency, owning "technology" (technology and innovation) is one of the keys to increasing resources. Ensuring this is a single factor that is important for human resource management because an organization must be able to identify improvements in its human resources. So, the main objective of this paper is to analyze the influence of current technology on HR processes, consider the existing literature on the topic, and its advantages and efficiency. In this scenario, there is a need to clearly identify a technology for efficient human resource management that is capable of enhancing employee skills. Many of the main areas of impact of technology on human resource development are discussed in order to obtain innovative human resource development.